Implementación de voz sobre protocolo de internet ip en la Cooperativa De Ahorro Y Crédito 9 De Octubre Ltda, bajo el estándar h323 version 4 - Vega Barriga, Kléver Hernán (2008)
At present, public and private institutions have seen the need to exploit resources, both hardware and software to develop in the technological field. The "Implementation of Voice over IP in the Cooperativa de Ahorro y Crédito 9 de Octubre Ltda.” is a researched work based on the use of the network and bandwidth that the institution has in its three agencies located in Salcedo (Matrix), in Latacunga Agency (1) and Mulalillo Agency (2). The IP telephony is an immediate application of this technology in a manner that allows the realization of ordinary telephone calls over IP to other packages network using a PC, gateways and phones standards. In general, communication services - voice, fax, voice messaging applications - which are transported through IP networks, normally the Internet, instead of being transported line conventional telephone network.